A comparative overview of health and social care policy for older people in England and Scotland, United Kingdom (UK). (June 2023) - Aujla, Navneet; Frost, Helen; Guthrie, Bruce; Hanratty, Barbara; Kaner, Eileen; O'Donnell, Amy; Ogden, Margaret E.; Pain, Helen G.; Shenkin, Susan D.; Mercer, Stewart W.
Highlights: Four policy themes, and four cross-cutting themes, common to both countries, emerged. Themes were summarised and compared between the countries using Donabedian's structure-process-outcome model. Despite structural differences in care, policy direction was similar in both countries. There were similarities in performance and patient outcomes in England and Scotland. Limited health and social care data hinder policy evaluation and outcome comparisons. Abstract: Background: Responsibility for health and social care was devolved to Scotland in 1999 with evidence of diverging policy and organisation of care compared to England. This paper provides a comparative overview of major health and social care policies in England and Scotland published between 2011 and 2023 relating to the care of older people. Methods: We searched United Kingdom (UK) and Scotland government websites for macro-level policy documents between 2011 and 2023 relating to the health and social care of older people (aged 65+). Data were extracted and emergent themes were summarised according to Donabedian's structure-process-outcome model. Results: We reviewed 27 policies in England and 28 in Scotland. Four main policy themes emerged that were common to both countries. Two related to the structure of care: integration of care and adult social care reform. Two related to service delivery/processes of care: prevention and supported self-management and improving mental health care. Cross-cutting themes included person-centred care, addressing health inequalities, promoting use of technology, and improving outcomes. Conclusion: Despite differences in the structure of care, including more competition, financial incentivization, and consumer-based care in England compared to Scotland, there are similarities in policy vision around delivery/processes of care (e.g. person-centred care) and performance and patient outcomes. Lack of UK-wide health and social care datasets hinders evaluation of policies and comparison of outcomes between both countries.